An introduction to randomization for clinical trials 1 - Rosenberger, William (Henry Stewart Talks, 2016)
Complete randomization, Forced balance procedures, Blocked procedures, Adaptive procedures, Comparison of procedures, Balancing properties, Comparability on unknown covariates, Predictability, Trade-off plots